2015
DOI: 10.1155/2015/260465
|View full text |Cite
|
Sign up to set email alerts
|

Acute Respiratory Distress Syndrome: Role of Oleic Acid‐Triggered Lung Injury and Inflammation

Abstract: Lung injury especially acute respiratory distress syndrome (ARDS) can be triggered by diverse stimuli, including fatty acids and microbes. ARDS affects thousands of people worldwide each year, presenting high mortality rate and having an economic impact. One of the hallmarks of lung injury is edema formation with alveoli flooding. Animal models are used to study lung injury. Oleic acid-induced lung injury is a widely used model resembling the human disease. The oleic acid has been linked to metabolic and infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
80
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 73 publications
1
80
0
1
Order By: Relevance
“…In this study, we evaluated the impact of propofol on OA-induced ALI in rats. Consistent with results of previous studies 21 , results of this study show that propofol can significantly reduce OA-induced ALI. We also found that HO-1 was strongly expressed in the propofol-pretreated lung tissue, which can significantly improve PaO 2 , significantly decrease lung W/D weight ratio, lung injury, and apoptosis of AT-II in OA rats.…”
Section: ■ Discussionsupporting
confidence: 93%
“…In this study, we evaluated the impact of propofol on OA-induced ALI in rats. Consistent with results of previous studies 21 , results of this study show that propofol can significantly reduce OA-induced ALI. We also found that HO-1 was strongly expressed in the propofol-pretreated lung tissue, which can significantly improve PaO 2 , significantly decrease lung W/D weight ratio, lung injury, and apoptosis of AT-II in OA rats.…”
Section: ■ Discussionsupporting
confidence: 93%
“…This suggests the mechanisms other than cytokine inhibition mediated neutrophil chemoattraction. OA is proved to increase chemokines CXCL-8 and MIP-1α in lung tissue [56]. Oral OA induces CXCL-3 release and neutrophil-endothelium interaction in the air pouch [57].…”
Section: Discussionmentioning
confidence: 95%
“…Human subjects who develop ARDS have higher plasma levels of C18 unsaturated fatty acids (16). Injection of high concentrations of oleic acid causes rapid high permeability lung edema with in ammation and impaired gas exchanges and mechanics (17) reproducing human ARDS. Lung injury occurs rapidly after less than 5 minutes (18) with neutrophils in ltration and production of cytokines and chemokines (17).…”
Section: Discussionmentioning
confidence: 99%
“…Injection of high concentrations of oleic acid causes rapid high permeability lung edema with in ammation and impaired gas exchanges and mechanics (17) reproducing human ARDS. Lung injury occurs rapidly after less than 5 minutes (18) with neutrophils in ltration and production of cytokines and chemokines (17). The acute lung damage caused by oleic acid is characterized by important neutrophils accumulation and activation leading to intense in ammation (17), concordant with the pathophysiology of human ARDS (2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation